Reconstruction of the anterior cruciate ligament using the Press‐Fit‐Hybrid technique—A cohort study with an up to 10‐year follow‐up - Niko Schauer; Martin Fischer; Rejane Golbach; David A. Groneberg; Fabian Holzgreve; Daniel Niederer; Daniela Ohlendorf; Adalbert Missalla (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose To examine the long‐term results of the Press‐Fit‐Hybrid fixation technique in anterior cruciate ligament (ACL) reconstruction on self‐reported knee function, sport ability, return to sport (RTS) success, quality of life and re‐rupture rates. Methods Adults with ACL rupture which was reconstructed between 2011 and 2013 using the Press‐Fit‐Hybrid fixation technique were included. Participants completed questionnaires before surgery and at 6‐month, 1‐year, 2‐year, 3‐year and 10‐year follow‐ups. Subjective knee function was self‐reported using the International Knee Documentation Committee (IKDC) and Lysholm scores. The level of sport activities was assessed using the Tegner Activity Scale (TAS), and quality of life was evaluated with the Knee injury and Osteoarthritis Outcome Score Quality of Life subscale (KOOS‐QoL). RTS success rates were categorised into return to participation, RTS and return to performance. Results Participants (N = 135) (81 males, 54 females; aged 32.3 years [SD 11.7]) were included. Mean scores at 2, 3 and 10 years were for IKDC 87.6 (SD 10.5), 89.2 (SD 11.0) and 86.5 (SD 14.8), while for Lysholm 92.1 (SD 8.4), 93.3 (SD 7.8) and 90.6 (SD 12.3). The KOOS‐QoL averaged 80.4; 70.0% scored above 80.0. After 3 years, 73% returned to their pre‐injury TAS‐level; 52% still performed at the pre‐injury level after 10 years. Average return to participation was within 5.9 months. 96% returned to sport within 9.6 months on average. 72% returned to performance within a mean of 12.2 months. Re‐rupture rates were 2.85% in the first 3 years and 5% between 3 and 10 years post‐surgery. Conclusion Press‐Fit‐Hybrid leads to low re‐rupture and high RTS rates, restoring knee functionality and improved quality of life. Preliminary results need validation in a randomised controlled trial. Level of Evidence Level III.